(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
The yield advantage obtained due to intercropping is attributed to a better use of resources by crops grown in combinations, as compared to sole stands. Field experiment conducted at Gimbo and Guraferda during 2017 and 2018 cropping seasons in order to determine the appropriate intercropping row arrangement on maize-common bean yield and economic advantages of the cropping system. Maize variety BH-540 and common bean variety Hawassa dume were used as test crop. The experiment used four treatments (sole maize, sole common bean, 1:1 maizecommon bean and 1:2 maize-common bean intercropping) arranged in a randomized complete block design with four replications. Grain yield of the component crops were significantly varied by locations. The highest maize yield was recorded at Guraferda than Gimbo; whereas, common bean yielded better at Guraferda than at Gimbo. The combined mean grain yield of maize and common bean was significantly (p<0.05) higher for sole stands than intercropping. The highest yield of 6545.7 and 5570.6 kg ha-1 was obtained from sole maize at Guraferda and Gimbo locations, respectively. On the other hand, the highest yield of 3407.2 and 2638.0 kg ha-1 was obtained from growing sole common bean at Gimbo and Guraferda locations, respectively. The yield obtained from 1:1 maize-common bean intercropping was statistically same with sole maize yield at Guraferda. The highest LER of 1.62 and 1.52 with MAI of 15,268.05 and 13.695.90 ETB ha-1 obtained from 1:1 maize-common bean intercropping at Guraferda and Gimbo locations, respectively. Generally, growing 1:1 maize-common bean intercropping found to be more productive and economically profitable than others. Hence, a one row common bean intercropped between the two rows of maize can be recommended in the lowlands of Gimbo and Guraferda areas. Int. J. Agril. Res. Innov. Tech. 10(1): 22-27, June 2020